THE DESIGN OF TEACHING MATERIALS FOR ONLINE INTERACTION ACTIVITIES WITH THE HELP OF CHATGPT: THE CASE OF ROMANIAN AS A FOREIGN LANGUAGE - URSA, Anca; MIHAI, Mihaela; ALBERT, Narcisa (Studia Universitatis Babeș-Bolyai Philologia, 2025)
The Design of Teaching Materials for Online Interaction Activities with the Help of ChatGPT: The Case of Romanian as a Foreign Language. This study explores the role of ChatGPT, the most widely used current chatbot, in designing teaching materials for modern language instruction, with a focus on Romanian as a foreign language (RFL). The research aims to assess the usefulness and capabilities of this AI tool from the perspective of the teacher as a curriculum designer. The linguistic activity under analysis—online interaction—was only recently included in the Common European Framework of Reference for Languages (CEFR), Companion Volume (2018), and involves a multimodal approach to communication. Within this framework, the study investigates how CEFR grids for online interaction can be effectively used to create didactic scenarios tailored to international learners of Romanian. By applying techniques such as the "funnel strategy" and "progressive-hint prompting", the research generated a series of B1-level instructional activities with the help of ChatGPT, simulating authentic online communication contexts (e.g., collaborating in a chat group to plan an event). The results show that, under teacher guidance, ChatGPT can be an effective partner in designing interactive, relevant, and motivating materials that enhance learners’ ability to engage in real-life online interactions. The study highlights both the potential and the current limitations of AI-assisted material development, emphasizing the need for a critical and reflective approach to using such tools in language education. REZUMAT. Designul materialelor în activitatea de interacțiune online cu ajutorul lui chatgpt. Cazul românei ca limbă străină. Studiul investighează rolul pe care ChatGPT, cel mai utilizat chatbot actual, îl poate avea în proiectarea materialelor didactice pentru predarea limbilor moderne, cu accent pe româna ca limbă străină (RLS). Cercetarea își propune să evalueze utilitatea și competențele acestui instrument de inteligență artificială, din perspectiva profesorului ca autor de curriculum. Activitatea lingvistică analizată – interacțiunea online – este una relativ recent inclusă în Cadrul European Comun de Referință pentru Limbi (CECRL), Companion Volume (2018), și presupune o abordare multimodală a comunicării. În contextul respectiv, studiul explorează modul în care grilele CECRL pentru interacțiunea online pot fi valorificate în proiectarea de scenarii didactice relevante pentru cursanții internaționali care învață limba română. Prin aplicarea tehnicilor de tip „strategia pâlniei” și „progressive-hint prompting”, cercetarea a generat, cu ajutorul ChatGPT, o serie de activități didactice adaptate nivelului B1, care simulează situații autentice de comunicare online (de exemplu, colaborarea într-un grup de chat pentru organizarea unui eveniment). Rezultatele indică faptul că, sub ghidajul profesorului, ChatGPT poate deveni un partener eficient în elaborarea de materiale interactive, relevante și motivate pentru studenți, favorizând dezvoltarea competențelor de interacțiune online într-un mediu autentic. Studiul evidențiază atât potențialul, cât și limitele actuale ale implicării AI în proiectarea didactică, subliniind necesitatea unei utilizări critice și reflexive a acestui instrument. Cuvinte-cheie: inteligență artificială, ChatGPT, predarea limbilor străine, designul materialelor, româna ca limbă străină, interacțiune online, CECRL Article history: Received 15 November 2024; Revised 19 April 2025; Accepted 27 April 2025; Available online 10 June 2025; Available print 30 June 2025.